2016
DOI: 10.3109/08880018.2016.1173147
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus disease in children with acute lymphoblastic leukemia

Abstract: Viral infections are an underrecognized problem in children on standard chemotherapy for acute lymphoblastic leukemia (ALL). In countries with high baseline seroprevalence of cytomegalovirus (CMV) such as India, it may be an important pathogen leading to fever, end-organ damage, and cytopenia. Data regarding the incidence and manifestations of CMV disease in pediatric ALL patients are scanty. The authors prospectively assessed all children on chemotherapy for ALL with prolonged febrile neutropenia (FN) for CMV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 24 publications
0
33
1
Order By: Relevance
“…In one study, CMV antigenemia for hematologic malignancies had been shown at a rate of %11 (6) . Jain et al (2) had found a 10% risk of CMV infection in their study performed in children with ALL and prolonged febrile neutropenia. Thirteen of fourteen patients in our study had positive CMV IgG results which were considered as reactivation of CMV.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In one study, CMV antigenemia for hematologic malignancies had been shown at a rate of %11 (6) . Jain et al (2) had found a 10% risk of CMV infection in their study performed in children with ALL and prolonged febrile neutropenia. Thirteen of fourteen patients in our study had positive CMV IgG results which were considered as reactivation of CMV.…”
Section: Discussionmentioning
confidence: 95%
“…Cytomegalovirus disease may have nonspecific manifestations as fever, malaise, abnormal blood counts, elevated transaminases; and also serious outcomes like hepatitis, colitis, pneumonitis, retinitis or even death in immunocompromised patients. In the literature, fever had been shown as the most common symptom of CMV disease in children with ALL (2,3) . In our study, fever (64%) was found as the most common symptom supporting previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34,36,[39][40][41][42][43] CMV pneumonia is much less common in patients who have received an autologous transplant, or in patients receiving treatment of HM with incidence of 1% to 5% reported in the absence of surveillance and preemptive therapy. [44][45][46][47][48] Treatment Ganciclovir (5 mg/kg intravenous [IV] every 12 hours) remains the first-line treatment for CMV pneumonitis. 49 Based on the results of three nonrandomized studies, [50][51][52] CMV immunoglobulin was often recommended as adjunctive treatment.…”
Section: Cytomegalovirus Epidemiologymentioning
confidence: 99%